Schneider-Mayerson, M., & Bellamy, B.R. (Eds). (2019). An Ecotopian Lexicon. - Ibe, Kathleen (Journal of Ecohumanism, 2023)
Schneider-Mayerson, M., & Bellamy, B.R. (Eds). (2019). An Ecotopian Lexicon. University of Minnesota Press.